Espaços de memória e identidade feminista no Instagram: análise a partir de coletivos feministas - Viana, Anna Raquel de Lemos (2021)
With the changes that occurred in the last decades, mainly due to the convergence of the media and the emergence of new sociability and possibilities with the advent of technologies, the influence and ruptures in the social organization are perceived. To accompany social, informational, and digital development, women - in their subversive dimension - seek to break fissures to modify the public space and build new social roles through new skills and abilities with technologies and the Internet, which increasingly is part of the subjects' daily lives, although still unequally and exclusively. In this research, it was proposed to understand the digital social network Instagram as a space of memory and identity of three feminist collectives in the city of João Pessoa / PB, with different insertions: women linked to the university; to the market; without a structural link. It is guided by the interest in enabling new points of view on the complex phenomenon of memory that is intrinsically related to identity. The space of memory is considered to be the space to re-signify, construct, and reconstruct representations and identities traversed by social representations, historically engendered in society. The theoretical dimension that supports the investigation is centered on four intertwined axes: memory as a field of study; the Internet - specifically Instagram - as a technology that is changing behaviors and enabling new memory spaces; and the identity, which has been affected by these new behaviors, added to the notions of gender, feminism, and intersectionality. From the feminist perspective, collectives of women who work to build a democratic society and with gender equality are analyzed, based on new narratives. To achieve the objective, the qualitative approach methodology was structured as to the source as field research, through virtual ethnography, to understand the specific characteristics of João Pessoa's feminist collectives on Instagram. As for the objective, descriptive. For this purpose, individual semi-structured interviews with women who made up the coordination and management of profiles on Instagram were used as data collection instruments. To analyze and treat the data, we opted for the Collective Subject Discourse Analysis (CSD), a method that consists of rescuing significant social representations present. The study indicated that Instagram corresponds to the points exposed and addressed by Pierre Nora (1993), it is understood as a place of memory and that collectives served to give voice to the identity of women as feminists and maximize their actions on Instagram, allowing a space of collective representation and agency, in which they use information and memory as an imperative for the relationship of a political and social subjectivity with awareness actions promoting the empowerment of women.